The Effect of Work Motivation and Flexibility on Performance through Job Satisfaction as an Intervening Variable (A Study on Gojek Partner Drivers in Surabaya) - Diva Rihhadatul ‘Aisy; Budi Prabowo (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to determine and analyze the influence of work motivation and flexibility on performance through job satisfaction as an intervening variable. This research is an associative type with a quantitative approach. Through SEM-PLS analysis, path analysis, bootstrapping analysis, and mediation analysis, it was found that partially, work motivation and flexibility had a positive and significant effect on performance, work motivation had a positive and significant effect on job satisfaction, flexibility had a negative and insignificant effect on satisfaction. work, as well as work motivation and flexibility partially do not have a significant effect on performance through job satisfaction.